Recursos de realidade virtual e aumentada em sala de aula: uma perspectiva de uso das tecnologias digitais no processo de ensino e aprendizagem - Patrícia Rabelo Goulart (2022)
This dissertation was developed from the need to develop viable alternatives for the application of digital technologies in education, among the various technological innovations, the use of Virtual and Augmented Reality was investigated. These resources are considered one of the most advanced forms of human-computer interface and have three-dimensional graphic images, overlapping the limits of computer interfaces that are restricted to the two-dimensional space of the screens. The objective was to investigate, from the perception of teachers and students, the development and implementation of an interdisciplinary teaching plan from the perspective of active learning, which incorporates the use of these technologies. To this end, a field study was conducted in a school in Minas Gerais. The research methodology was characterized by a qualitative approach and data collection was done through three strategies: participant observation, questionnaire and semi-structured interview. It is noteworthy that this study took place in the period of the worldwide dissemination of a new disease and the fieldwork was carried out in the return face-to-face, after a long period of suspension of classes due to physical distancing measures adopted as a way to prevent COVID-19. As research results, it was found that the use of resources is relevant to the construction of school knowledge and the autonomy of students, to the extent that they became co-responsible for the progress of the classes. It also proved to be challenging, mainly because of the apprehension of the school community that had to adapt, in a hurry, to the pandemic reality. Other difficulties were faced, such as: the short time to plan and execute the classes, the initial insecurity of the participants in using technological resources and methodologies that are not very present in the school environment. As an educational resource, we proposed the production of an e-book containing the lesson plans collectively developed during the course of this research, so that this material can contribute to the practice of teachers who are interested in the theme.